Pengaruh Etika Bisnis Islam Terhadap Kesejahteraan Pedagang (Studi Kasus Pedagang Pusat Pasar Medan) - Ya’ti Ikhwani Nasution (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
The purpose of this study is to find out whether there is an influence of Islamic business ethics with the variables of unity, equilibrium, free will, responsibility, benevolence and the welfare of traders in the Pusat Pasar Medan. This research is a quantitative research and the analysis used is multiple regression analysis. The data collection technique used is the questionnaire method obtained directly from the respondent, namely the Pusat Pasar Medan Trader. Analyzed using statistical tools, namely SPSS Version 22. Based on the results of data processing has shown that there is a significant influence as partially and simultaneously among the unity, equilibrium, free will, responsibility and benovelence towards the welfare of traders in the Medan Market Center. For unity, free will, responsibility and benovelence have a positive effect on the welfare of traders in Medan Market Center. While the equilibrium variable has a negative effect on the welfare of Medan Market Center traders. The adjusted R square value is 0.345. This means that 34.5% increase in welfare can be explained by independent variables, namely the variables of unity, equilibrium, free will, responsibility and kindness. While 65.5% is explained by other factors.